Phytochemical analysis and in vitro anti-proliferative activity of Viscum album ethanolic extracts - Carla Holandino; Michelle Nonato de Oliveira Melo; Adriana Passos Oliveira; João Vitor da Costa Batista; Marcia Alves Marques Capella; Rafael Garrett; Mirio Grazi; Hartmut Ramm; Claudia Dalla Torre; Gerhard Schaller; Konrad Urech; Ulrike Weissenstein; et al. (BMC, 2020)
Abstract Background Viscum album L. (Santalaceae), commonly known as mistletoe, is a hemiparasitic plant traditionally used in complementary cancer treatment. Its antitumor potential is mostly attributed to the presence of aqueous soluble metabolites; however, the use of ethanol as solvent also permits the extraction of pharmacological compounds with antitumor potential. The clinical efficacy of mistletoe therapy inspired the present work, which focuses on ethanolic extracts (V. album "mother tinctures", MT) prepared from different host trees. Methods Samples from three European subspecies (album, austriacum, and abietis) were harvested, and five different V. album-MT strains were prepared. The following phytochemical analyses were performed: thin layer chromatography (TLC), high-performance liquid chromatography (HPLC) and liquid chromatography-high resolution mass spectrometry (LC-HRMS). The proliferation assay was performed with WST-1 after incubation of tumor (Yoshida and Molt-4) and fibroblast cell lines (NIH/3 T3) with different MT concentrations (0.5 to 0.05% v/v). The cell death mechanism was investigated by flow cytometry (FACS) using Annexin V-7AAD. Results Chemical analyses of MT showed the presence of phenolic acids, flavonoids and lignans. The MT flavonoid and viscotoxin contents (mg/g fresh weight) were highest in Quercus robur (9.67 ± 0.85 mg/g) and Malus domestica (3.95 ± 0.58 mg/mg), respectively. The viscotoxin isoform proportions (% total) were also different among the VA subspecies with a higher content of A3 in V. album growing on Abies alba (60.57 ± 2.13). The phytochemical compounds as well as the viscotoxin contents are probably related to the antitumor effects of MT. The cell death mechanisms evaluated by colorimetric and FACS methodologies involved necrotic damage, which was host tree-, time- and dose- dependent, with different selectivity to tumor cells. Mother tincture from V. album ssp. abietis was the most effective at inducing in vitro cellular effects, even when incubated at the smallest concentration tested, probably because of the higher content of VT A3. Conclusion Our results indicate the promising antitumor potential of Viscum album ethanolic extracts and the importance of botanical and phytochemical characterization for in vitro anti-proliferative effects.